(untitled) (Journal of Laboratory Animal Science, 2024)
Small laboratory animal models are being increasingly used as a biomedical research tool in several human diseases such as cancer, cardiovascular diseases, endocrine disorders and obesity. For the last couple of years, molecular and functional imaging become a powerful techniques for studying spatial and temporal distribution of new drugs and their target affinity non-invasively in animal models. Hence non invasive imaging modalities such as positron emission tomography (PET), single photon emission computed tomography (SPECT), X-ray, magnetic resonance imaging, fluorescence and bioluminescence have emerged for rapid and accurate screening of the new molecules. This review focuses on nuclear imaging modalities mainly SPECT and PET, which allow whole body survey of the animal and quantitation of target affinity. While establishing such facilities, accessibility to vivarium, work flow, availability of radiotracers, regulatory requirements and trained human resource needs to be considered. The readout data requires dedicated software for viewing and quantitation eg. VIVID, PMOD, AMIDE and Micro View. Therefore, a perfect amalgamation of instrumentation, facility logistics and work flow that is required for efficiently managing such a facility has been elaborately reviewed in this article.